2023
DOI: 10.1038/s41684-023-01124-1
|View full text |Cite
|
Sign up to set email alerts
|

A mapping review of refinements to laboratory rat housing and husbandry

Abstract: Refining the housing and husbandry of laboratory rats is an important goal, both for ethical reasons and to allow better quality research. We conducted a mapping review of 1,017 studies investigating potential refinements of housing and husbandry of the laboratory rat to assess what refinements have, and haven't, been studied, and to briefly assess whether there is evidence to support any impact on rat welfare. Among the many refinements studied, the majority involve changes to the cage, but some also involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 127 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Providing a stimulating environment that fits species-specific needs improves the wellbeing of laboratory rodents (summarized by Smith and Corrow, 2005 ; Neville et al, 2023 ). It has been shown that the benefits of EE for wild-type rodents and animal models of brain disorders are multilevel, encompassing visual, motor, cognitive, and somatosensory systems (for a review, see Nithianantharajah and Hannan, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing a stimulating environment that fits species-specific needs improves the wellbeing of laboratory rodents (summarized by Smith and Corrow, 2005 ; Neville et al, 2023 ). It has been shown that the benefits of EE for wild-type rodents and animal models of brain disorders are multilevel, encompassing visual, motor, cognitive, and somatosensory systems (for a review, see Nithianantharajah and Hannan, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Providing a stimulating environment that fits species-specific needs improves the wellbeing of laboratory rodents (summarized by Smith and Corrow, 2005;Neville et al, 2023). It has been shown that the benefits of EE for wild-type rodents and animal .…”
Section: Enlarged Suprapyramidal and Infrapyramidal Mossy Fibers Afte...mentioning
confidence: 99%
“…Rat housing has been extensively studied with cage type and contents being the most investigated housing refinement ( Neville et al, 2023 ). Previous studies have shown that environmental enrichment (EE; where housing is enhanced with additional objects to interact with and the size of the cage may also be increased) reduces stress in laboratory animals, and improves depressive-live behaviours and performance in learning and memory tests ( Simpson and Kelly, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, an accurate determination of the impact of the behavior management program can only be made if multiple assessments are conducted over time. For example, animals may lose interest in some forms of resources provided and return to exhibiting abnormal behaviors; social interactions may evolve as animals age, which could result in incidents of conflict that require other adjustments; or other changes in external factors (e.g., changes in personnel, change in animal composition in the primary enclosure or room) may have an effect on the welfare of the animal [ 126 ]. The frequency and type of assessment should be based on the species of animal, type of research being conducted on the animal, and its baseline behaviors, among other factors [ 18 ].…”
Section: Monitoring the Impact Of Research Animal Behavior Management...mentioning
confidence: 99%